Seed protectant potential of Mitracarpus villosus and Phyllanthus fraternus extracts on germinative capability of stored food grains - Adesina, J. M.; Rajashekar, Y.; Ofuya, T. I.; Ashamo, O. M.; Ileke, K. D. (International Journal of Horticultural Science, 2019)
Seed storage is an essential post-harvest operation that decides the success of seeds viability and germination in next generation. The study explored Mitracarpus villosus and Phyllanthus fraternus extracts as bio-insecticides seed treatments on stored wheat and green gram seeds viability and germination. M. villosus and P. fraternus plants powder were sequentially extracted with solvents of increasing polarity (Petroleum ether, hexane, ethyl acetate, acetone, chloroform and methanol), concentrated and tested for insecticidal activity by fumigant toxicity. The extract which showed maximum activity, was selected for seed viability and germination test. Five replications each were made for the treatment and the control. The plant extracts strengthen the non-phytotoxic nature of plant products against seed viability and germination. Seeds treated with extracts (50-400 μg seed-1) did not lose their viability as it resulted in successful and normal germination within the range of 90 – 97.67% irrespective of the extracts concentration. While, seeds in control recorded 95.55 and 100% germination which were not significantly different (P>0.05) compared to the treated seeds. Based on findings from the study, potential exploitation of M. villosus and P. fraternus as food grains protectant in insect pest management strategies is recommended for the resource poor farmers. However, further investigations are suggested on biosafety and effects of the extracts on the organoleptic contents of the grains prior to consumption.